2023
DOI: 10.1039/d2ra04847g
|View full text |Cite
|
Sign up to set email alerts
|

Responses of aquatic vegetables to biochar amended soil and water environments: a critical review

Abstract: The effects of biochars on aquatic vegetables and soil/water environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 99 publications
0
3
0
2
Order By: Relevance
“…Biochar and biogas slurry are widely used to improve agricultural soil, which can improve soil properties and affect the migration of soil nutrients ( Guo et al., 2014 ; Liang et al., 2023 ). At present, the research on the application of biochar and biogas slurry is mainly focused on the improvement of dryland soil properties ( Liao et al., 2022 ; Zhang et al., 2022 ; Ren et al., 2023 ), the effect on the properties of flooded soil is rarely investigated ( Wang et al., 2023 ). This study focused on exploring the persistent effects of biochar and biogas slurry co-application on soil nitrogen nutrients and lotus root growth characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Biochar and biogas slurry are widely used to improve agricultural soil, which can improve soil properties and affect the migration of soil nutrients ( Guo et al., 2014 ; Liang et al., 2023 ). At present, the research on the application of biochar and biogas slurry is mainly focused on the improvement of dryland soil properties ( Liao et al., 2022 ; Zhang et al., 2022 ; Ren et al., 2023 ), the effect on the properties of flooded soil is rarely investigated ( Wang et al., 2023 ). This study focused on exploring the persistent effects of biochar and biogas slurry co-application on soil nitrogen nutrients and lotus root growth characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that green oxygen-carrying biochar could improve water quality and reduce N 2 O emissions [14,15]. At the same time, its unique microporous structure provides an ideal habitat for microorganisms [16], and biochar is able to improve the soil microenvironment, soil microorganism, and soil enzyme activities [17,18]. However, biochar may inhibit the growth of microorganisms due to the adsorbed soil organic carbon and other low-molecular-weight organic matter [19].…”
Section: Introductionmentioning
confidence: 99%
“…Biochar impacts plant growth [16]. Biochar is applied in aquatic vegetable cultivation, and it not only improves the quality and yield, but also reduces the edible risk [18]. However, Chi et al [11] suggested that biochar's amendment to sediments had a negative effect on the growth of Vallisneria spiralis L. In the presence of polycyclic aromatic hydrocarbons (PAHs), the adsorption of biochar made the PAHs more persistent in water [11,20].…”
Section: Introductionmentioning
confidence: 99%
“…Vale ressaltar que as propriedades, caracterizações e aplicações do biocarvão continuam sendo pesquisadas e estão descritas em artigos de revisão de 2020 a 2023, segue algumas dessas referências: ALBALASMEH et al, 2020;YAASHIKAA et al, 2020;HU et al, 2020;TOMCZYK;SOKOŁOWSKA;BOGUTA, 2020;AKHIL et al, 2021;CARNIER et al, 2021;AMIN et al, 2021;CHEN et al, 2021;YANG et al, 2022;CAIRNS et al, 2022;GURAV et al 2022;HERNANDES et al, 2022.QIU et al, 2022ADEGOKE et al, 2022;SHAHEEN et al, 2022;WANG et al, 2023.…”
Section: Fosfatounclassified
“…Após a pirólise, as bandas principais da amostra de biomassa desapareceram em grande parte devido à rápida remoção de compostos voláteis como resultado do grau acelerado e intensificado da carbonização que ocorre nas temperaturas empregadas na pirólise e, portanto, os espectros tornaram-se mais simplificados (WANG;COA;WANG, 2009;SHAABAN et al, 2013). Figura 44 -Espectro de infravermelho da amostra de biocarvão Fonte: arquivo da autora.…”
Section: Capacidade De Troca Catiônica (Ctc)unclassified